Get Noticed to Get Ahead: The Impact of Personal Branding on Career Success - Gorbatov, Sergey; Khapova, Svetlana N.; Lysova, Evgenia I. (Frontiers in Psychology, 2019)
With growing attention to personal branding, as effective career behavior, little is known about the factors that predict personal branding behaviors and its outcomes. In two studies (N = 477) across two distinctly different cultural contexts (Western and Asian) based on a newly developed and validated scale of personal branding, we examine the antecedents and outcomes of personal branding. The findings confirm that personal branding leads to greater career satisfaction, fully mediated by perceived employability. Career achievement aspiration was the strongest predictor of engaging in personal branding, while career feedback negatively related to personal branding intention and career self-efficacy positively related to personal branding but not to personal branding intention. These findings highlight the importance of personal branding as a contemporary career technique in promoting one's personal brand identity to achieve beneficial career outcomes.